Sodium Alginate Microneedles Loaded with Vancomycin for Skin Infections - Juhaina M. Abu Ershaid; Han Zhang; May Tayyem; Akmal H. Sabri; Ryan F. Donnelly; Lalitkumar K. Vora (Journal of Functional Biomaterials)
Background: Skin and soft tissue infections (SSTIs) present significant treatment challenges. These infections often require systemic antibiotics such as vancomycin, which poses a risk for increased bacterial resistance. Topical treatments are hindered by the barrier function of the skin, and microneedles (MNs) offer a promising solution, increasing patient compliance and negating the need for traditional needles. Methods: This study focused on the use of sodium alginate MNs for vancomycin delivery directly to the site of infection via a cost-effective micromolding technique. Dissolving polymeric MNs made of sodium alginate and loaded with vancomycin were fabricated and evaluated in terms of their physical properties, delivery ability, and antimicrobial activity. Results: The MNs achieved a 378 μm depth of insertion into ex vivo skin and a 5.0 ± 0 mm zone of inhibition in agar disc diffusion assays. Furthermore, in ex vivo Franz cell experiments, the MNs delivered 34.46 ± 11.31 μg of vancomycin with around 35% efficiency, with 9.88 ± 0.57 μg deposited in the skin after 24 h. Conclusions: These findings suggest that sodium alginate MNs are a viable platform for antimicrobial agent delivery in SSTIs. Future in vivo studies are essential to confirm the safety and effectiveness of this innovative method for clinical use.